2016
DOI: 10.21273/hortsci11275-16
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality of Field-grown Tomato Fruit as Affected by Grafting with Interspecific Hybrid Rootstocks

Abstract: In this study, the effects of grafting with interspecific hybrid rootstocks on field-grown tomato fruit quality were evaluated over a 2-year period. Fruit quality attributes from determinate ‘Florida 47’ tomato plants grafted onto either ‘Beaufort’ or ‘Multifort’ rootstocks were compared with those from non- and self-grafted controls. Grafted plants had higher fruit yields than non- and self-grafted plants, and increased production of marketable fruit by ≈41%. The increased yield was accompanied by few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 57 publications
7
44
1
6
Order By: Relevance
“…For example, tomato cv. ‘Florida 47’, grafted on ‘Beaufort’ and ‘Multifort’ rootstocks, increased the marketable fruit yield by up to 41% . A significant decrease in the yield and number of fruit was observed when eggplant rootstock was used…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, tomato cv. ‘Florida 47’, grafted on ‘Beaufort’ and ‘Multifort’ rootstocks, increased the marketable fruit yield by up to 41% . A significant decrease in the yield and number of fruit was observed when eggplant rootstock was used…”
Section: Resultsmentioning
confidence: 99%
“…'Florida 47', grafted on 'Beaufort' and 'Multifort' rootstocks, increased the marketable fruit yield by up to 41%. 28 A significant decrease in the yield and number of fruit was observed when eggplant rootstock was used. 10 Krumbein and Schwarz 7 reported that tomato yield was significantly reduced under shading, thus the commercial rootstocks were not able to enhance the yield reduction.…”
mentioning
confidence: 99%
“…Tomato fruit contains significant amounts of ascorbic acid, and several studies showed that fruit content strongly reduced by grafting both in greenhouse and field studies (Fernández-García et al, 2004a,b; Arvanitoyannis et al, 2005; Di Gioia et al, 2010; Vinkovic-Vrcek et al, 2011; Djidonou et al, 2016; Riga et al, 2016). Fruit vitamin C content was reduced in soil cultivation of different tomato scions grafted onto ‘Heman,’ ‘Spirit,’ ‘Arnold,’ ‘Beaufort’ (Qaryouti et al, 2007; Turhan et al, 2011) and in hydroponics using ‘Maxifort,’ ‘Interpro,’ or ‘King Kong’ rootstocks (Riga et al, 2016).…”
Section: The Configuration Of Fruit Quality In Grafted Vegetablesmentioning
confidence: 99%
“…The importance of the study of forest areas that have experienced hybridization has be pointed out, especially in order to identify the advantages of using hybrids for adaptation to extreme environments in which pure species trees have less vigor, a solution that can be used in reforestation programs (Zobel & Talbert, 1984;López-Upton et al, 2001;Wachowiak et al, 2016). Several studies also indicate that the vigor in plant species may be greater in hybrid offspring, at least in the first generation of hybridization (Djidonou et al, 2016;Xu et al, 2016;Zhang et al, 2019). Ávila-Flores et al (2016a) in their work on hybrid stands of trees in Durango, Mexico, in which the degree of hybridization between Pinus engelmannii x P. arizonica was studied, indicate that these hybrids may have the potential for adaptation in drought conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In grafting, the use of hybrids has been studied in conifer species (Marchal et al, 2017;Kita et al, 2018), however, in pines, it has not been studied much (Lott et al, 2003). In contrast, some plants, such as tomato and watermelon have been studied extensively, and survival levels greater than 80% have been reported (Djidonou et al, 2016;Xu et al, 2016;Zhang et al, 2019). Survival models are very useful to make predictions about the probability of survival and death through the time, as a function of two or more treatments (Kleinbaum & Klein, 2002;Zhang, 2016).…”
Section: Introductionmentioning
confidence: 99%